Flexible Fabrication of Flexible Electronics: A General Laser Ablation Strategy for Robust Large‐Area Copper‐Based Electronics. (6th August 2019) - Qin, Ruzhan; Hu, Mingjun; Zhang, Naibai; Guo, Zhongyue; Yan, Ze; Li, Jiebo; Liu, Jinzhang; Shan, Guangcun; Yang, Jun
Abstract: Attributed to high power density and controllable digital program operation, lasers are a powerful tool in the preparation, prototype fabrication, and post‐processing of materials. In this paper, a general laser ablation strategy that can be conducted under ambient, room‐temperature, and mask‐free conditions is employed for the rapid fabrication of robust large‐area copper‐based flexible electronics. Micrometer‐scale thick copper layer cladded on flexible polymer substrate can be removed efficiently in one laser scanning pass based on laser‐induced heat evaporation effect. Metal grids with a width less than 10 microns and a thickness close to 2 microns can be produced in a reliable manner. As proof‐of‐concept demonstrations, flexible transparent conducting electrodes and a variety of flexible circuit boards (FCBs) with different precisions and dimensions are fabricated by this approach in a digitally controlled mode and their photoelectric properties under normal and deformation states are investigated. The results indicate that the method is robust and as‐prepared flexible electrodes and circuits are reliable and endurable, indicative of the potential of this method in scalable fabrication of sub‐millimeter flexible electronics through a straightforward and flexible fashion. Abstract : A general laser ablation strategy conducted under ambient, room‐temperature, and mask‐free conditions is employed for the rapid fabrication of robust large‐area copper‐based flexible electronics. Flexible transparent conducting electrodes and a variety of flexible circuit boards with different precisions and dimensions can be produced in a fast and flexible manner, indicative of its great potential in fabricating sub‐millimeter flexible electronics.